Decision analytic economic paliperidone ER in relapsing schizophrenic patients in Italy - Berto, Patrizia; Negrini, Cristina; Ferrannini, Luigi (Farmeconomia. Health economics and therapeutic pathways, 2008)
Schizophrenia, with its typical chronic and relapsing course, is very burdensome, both clinically and economically. Its pharmacological management relies on two main drug classes: the older, or typical, antipsychotics, which are quite effective on positive symptoms, but limited by low tolerability and poor efficacy on negative symptoms, and atypical antipsychotics, which are better tolerated and effective on a wider range of psychotic symptoms. In this article, the authors briefly discuss current management options for patients with schizophrenia and highlight some unmet clinical needs in the field. After outlining the main clinical features shown by paliperidone ER, a novel antipsychotic, in its clinical development program, a decision analytic economic appraisal of its use in relapsing schizophrenic patients in Italy, as compared to the other available atypical antipsychotics, is presented. Under base-case assumption and after applying national costs and tariffs, the model predicts paliperidone ER to be associated with better clinical outcomes, expressed in terms of stable days, and lower costs; this means that paliperidone is dominant over the alternatives, according to the principles of economic evaluation of healthcare technologies. One-way sensitivity analyses conducted on structural and cost parameters indicated robustness of base-case estimates, which remain to be confirmed by “real world” national data.